The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/1574-6976.12047
|View full text |Cite
|
Sign up to set email alerts
|

Developmental biology ofStreptomycesfrom the perspective of 100 actinobacterial genome sequences

Abstract: To illuminate the evolution and mechanisms of actinobacterial complexity, we evaluate the distribution and origins of known Streptomyces developmental genes and the developmental significance of actinobacteria-specific genes. As an aid, we developed the Actinoblast database of reciprocal blastp best hits between the Streptomyces coelicolor genome and more than 100 other actinobacterial genomes (http://streptomyces.org.uk/actinoblast/). We suggest that the emergence of morphological complexity was underpinned b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 218 publications
(328 reference statements)
2
93
0
1
Order By: Relevance
“…Although morphological characteristics are typically important for Streptomyces identification, some studies have demonstrated that classification based on cell morphology, colony pigmentation, and physiological features do not always reflect the natural phylogenetic relationship between actinobacteria and related organisms [21]. Introduction of the polyphasic taxonomic approach combined molecular and biochemical analyses which elucidated streptomycetes systematics.…”
Section: Historical and Taxonomic Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although morphological characteristics are typically important for Streptomyces identification, some studies have demonstrated that classification based on cell morphology, colony pigmentation, and physiological features do not always reflect the natural phylogenetic relationship between actinobacteria and related organisms [21]. Introduction of the polyphasic taxonomic approach combined molecular and biochemical analyses which elucidated streptomycetes systematics.…”
Section: Historical and Taxonomic Aspectsmentioning
confidence: 99%
“…Introduction of the polyphasic taxonomic approach combined molecular and biochemical analyses which elucidated streptomycetes systematics. In addition, increased availability of 16S rRNA sequence data has enabled accurate studies of taxonomic affiliations and phylogenetic relationships [15,21,22].…”
Section: Historical and Taxonomic Aspectsmentioning
confidence: 99%
“…3). Moreover, translation of the PDE RmdB in S. coelicolor also seems to depend on BldA due to the presence of a TTA codon in rmdB (54). The regulation of several c-di-GMP metabolizing enzymes by the developmental regulators BldD, WhiA, and BldA further emphasizes the central role of c-di-GMP signaling in Streptomyces differentiation.…”
Section: C-di-gmp Turnover Enzymes Are Direct Targets Of Developmentamentioning
confidence: 97%
“…Orthologs of bldD show high conservation and local synteny and are found in all sporulating actinomycetes (54). Moreover, the c-di-GMP binding signature is present in all sequenced bldD orthologs and c-di-GMP is predicted to be present in all sporulating actinomycetes.…”
Section: Bldd Links C-di-gmp Signaling and Development In Streptomycesmentioning
confidence: 98%
See 1 more Smart Citation